P–627 Optimal timing of day 6 blastocyst transfer in artificially prepared frozen-thawed embryo transfer cycles. (6th August 2021) - Kim, H K; Ku, S.-Y; Kim, S H; Suh, C S; Kim, H
Abstract: Study question: When is the optimal timing of day 6 (D6) blastocyst transfer between the 6thday (P6)and the 7th(P7) day of progesterone administration in artificially prepared frozen-thawed embryo transfer(FET) cycle Summary answer: When transferring D6 blastocysts in artificially prepared FET cycles, live birth rate tended to be higher in P6 group than in P7 group. What is known already: Blastocyst transfer in FET cycles has increased due to several reasons including convenience for optimization of endometrial synchronization, improvement of laboratory techniques and preimplantation genetic testing. Meanwhile, D6 blastocyst which cryopreserved on day 6 after being developed to the full blastocyst stage, presented lower pregnancy outcomes in FET cycle than D5 blastocysts. However, there have been few studies on the optimal duration of progesterone administration when transferring D6 blastocysts. Study design, size, duration: This was a retrospective cohort study including patients who underwent frozen-thawed blastocyst transfer in artificially prepared cycles from January 2000 to May 2020. Patients with D6 blastocyst transfer on the 6th day of progesterone administration were included in D6-P6 group, and patients with D6 blastocyst transfer on the 7th day of progesterone administration were included in D6-P7 group. Participants/materials, setting, methods: Increasing dose of estradiol valerate was administered from the 3rd day of menstruation: 4 mg/day for the first four days, 6 mg/day for next four days, and then 8 mg/day until the confirmation of pregnancy. Progesterone was administered from the 14th day of menstruation if the endometrial thickness reached ≥7 mm. The independent t-test or Mann-Whitney test, chi-square test, and logistic regression analysis were performed. Main results and the role of chance: A total of 50 patients were included, and 13 patients underwent FET on P6 and 37 patients underwent FET on P7. Live birth rate was comparable between the P6 group and the P7 group (18.9% vs. 15.4%, p = 0.775). Live birth rate was higher in the D6-P6 group than in the D6-P7 group after adjusting for age, AMH, endometrial thickness on the starting day of progesterone administration and good embryo rate transferred with statistical significance (OR: 6.716, p = 0.005). Limitations, reasons for caution: Limitations of the present study is the retrospective design and the small sample size. Caution is needed in extrapolating results of this study because only intramural and vaginal progesterone supplementations were included in this study. Wider implications of the findings: Even if the duration of blastocyst formation was delayed, frozen-thawed D6 blastocyst may need to be considered for on P6 rather than P7. The difference of live birth rate is not statistically significant. This study should be acknowledged for the underestimation of the difference because of the small sample size. Trial registration number: Not applicable